Effects of Conditioning Temperature and Pellet Mill Die Speed on Pellet Quality and Relative Stabilities of Phytase and Xylanase - Caitlin E. Evans; Marut Saensukjaroenphon; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this experiment was to determine the effect of conditioning temperature and die speed on pellet quality and enzyme stability of phytase and xylanase. Treatments were initially arranged as a 2 × 3 factorial of conditioning temperature (165 and 185°F) and die speed (127, 190, and 254 rpm); however, when conditioning at 185°F it was not possible to pellet at 127 rpm. Thus, data were analyzed in 2 different segments using the GLIMMIX procedure of SAS. First, linear and quadratic contrasts were utilized to test the response to increasing die speed at 165°F. Second, the data were analyzed as a 2 × 2 factorial of conditioning temperature (165 and 185°F) and die speed (190 and 254 rpm). Treatments were arranged in a completely randomized design and replicated 3 times. Diets were conditioned for approximately 30 s and pelleted with a 3/16 in. diameter × 1 3/4 in. effective length die at a rate of 5 ton/h. Pellet durability index (PDI) was determined using the tumble box and Holmen NHP 100 methods. Samples of the unconditioned mash (M), conditioned mash (CM), and pellets (P) were collected and analyzed for phytase and xylanase concentration. Relative enzyme stabilities were expressed as CM:M and P:M. Stabilities expressed as P:M were used an indication of enzyme stability through the entire pelleting process. Diets conditioned at 165°F showed no evidence of difference in phytase or xylanase P:M stability when decreasing die speed from 254 to 127 rpm. However, when conditioning diets at 165°F, decreasing die speed increased (linear, P<0.001) PDI. There was no conditioning temperature × die speed interaction for overall xylanase P:M stability or PDI. However, there was a conditioning temperature × die speed interaction (P<0.01) for phytase P:M stability. When conditioning diets at 185°F, increasing die speed decreased phytase P:M stability. However, when conditioning at 165°F, increasing die speed did not influence phytase P:M stability. For main effects of conditioning temperature, increasing temperature improved (P<0.001) PDI with no evidence of difference for xylanase P:M stability. For the main effects of die speed (254 vs. 190 rpm), decreasing die speed decreased (P<0.001) the P:M xylanase stability, but there was no evidence of difference for PDI. The results of this trial indicate that die speed should be taken into consideration when evaluating enzyme stability of both phytase and xylanase as pellet mill models may be operating at different speeds. Additionally, increasing conditioning temperature will improve PDI, but may result in decreased phytase stability.
Keywords: die speed; pellet durability; enzyme stability; pellet; pellet mill; conditioning temperature; pellet quality; phytase; xylanase